Method to simulate transient pressure behaviors in subsea natural gas pipelines with a moving smart isolation device. (February 2023) - Zhang, Kang; Chen, Shengtao; Gong, Yongjun; Ning, Dayong; Zhang, Zengmeng
Highlights: A coupled dynamic mesh method is developed to simulate transient pressures in subsea maintaining gas pipelines with a moving smart isolation device. The proposed method is able to be coupled with the MOC, making it have the ability to incorporate affecting parameters and then handle complicated conditions. An experimental system has been conducted, and the proposed model has been validated using the experimental results to be accurate enough to simulate the transient pressures in gas pipelines with a moving object. Abstract: The pipeline maintenance technology using smart isolation devices is an effective mean to prevent potential accidents occurred in subsea natural gas pipelines. The devices need to move with the flowing fluid and finally stop at a desired location inside the pipe, to achieve successful communication with the external link. The sudden change of the moving velocity of the device may cause severe transient pressures, which is one of the determining factors of the moving process of the device and its final stopping location inside pipe. This paper proposes a method using a coupled dynamic mesh technique to simulate the transient pressure behaviors in natural gas pipelines with a moving device. The implicit and explicit coupled method has been developed to achieve the simulation of the moving interfaces and improve the ability of incorporating complex influence factors. Verifications have been conducted using the results from the experimental method, and the reasonable agreement between the results from these two methods validates that the proposed method can be used to simulate the transient pressure behaviors in gas pipelines with a moving device. The proposed simulation method coupling with the moving state of the device has been developed and applied to a practical case to predict the moving process and thus the final stopping location of the device.